Bias Patriarkhi dalam Hukum Keluarga Islam Sudan Tahun 1991 Mempertimbangkan Pengalaman Khas Perempuan untuk Perlindungan dari Diskriminasi - Husna, Khotimatul (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
The protection of women from discrimination in Islamic family law is a demand of women's rights fighters, but in Sudan this demand is not accepted because there is still a patriarchal bias in the articles of the 1991 Sudanese family law. These articles discriminate against women in various aspects, both social and biological, because of strong and deep-rooted patriarchal traditions. This study aims to explore eight discriminatory issues against women from articles of patriarchal bias in the 1991 Sudanese family law which views women's rights and obligations as different from those of men in the family. This study uses a descriptive analysis approach with the theory of essential justice proposed by Dr. Nur Rofiah Bill. Uzm. This theory sees women as whole human beings and equal subjects, so that true justice requires consideration of women's experiences which can be biologically and socially different from men's. Data obtained through literature review or library research. This study concludes that the discriminatory articles against women in the 1991 Sudanese Islamic family law are due to the fact that the family law was drafted by government authorities and a masculine societal culture and does not present women's unique experiences as a policy consideration. The reasoning of patriarchal culture in Sudanese family law completely ignores the impact of harm or harm on women. In the end, patriarchal bias articles in Sudanese family law have contributed to perpetuating gender inequality. This confirms that efforts to protect Sudanese women from acts of subordination, marginalization, stereotypes, violence, and double burden face serious challenges because they are legitimized by positive law. As a result, women occupy a weak and weakened position in the family. Keywords: Patriarchy, Sudanese Islamic Family Law